Analysis of training load and competition during the PhD course of a 3000-m steeplechase female master athlete: an autobiography - Elisa Gabrielli; Stefania Fulle; Giorgio Fano'-Illic; Tiziana Pietrangelo (PAGEPress Publications, 2015)
The first author, Elisa Gabrielli, has been a distance runner for many years, and then at a particular point in her career, she decided to move over to the 3000-m steeplechase. She was attracted by this discipline as she believed that it would be the appropriate discipline for her, due to the challenge it provided her, and the necessary knowledge and awareness she had through her studies. For reasons that are discussed in this report, the 3000-m steeplechase is a race that is more difficult to interpret and manage biomechanically and physiologically than most others. Combining this with her PhD allowed her to use a multidisciplinary approach to review the competitive experience gained in this discipline. During this period, she indeed not only deepened the technical aspects of her training, but also those that underlie this discipline, through her knowledge of sport, with particular reference to the female athlete. Through her technical research, she was able to take 'snapshots' of what could happen from the physiological point of view. With satisfaction, she improved her performance in the 3000-m race and in the 3000-m steeplechase. How? In particular, she worked on her running technique through specific exercises. She worked on de-contraction and posture, while saving energy consumption. She worked on the control of her breathing, and she took into account her prevailing heart rate. This was all in combination with the consumption of specific nutrients, as she tried to manage the production of lactate with the training of the red muscle fibres that are rich in mitochondria. Finally, she tried to improve her perception of strenuous work, by training at high altitude. This allowed her not only to improve her physical performance, but especially to improve her mind-set, which allowed her to be more confident in herself and her abilities.